A study on service quality dimensions toward customer satisfaction of Unifi in Selangor / Norhalizatul Akma Diana Abdul Aziz - Abdul Aziz, Norhalizatul Akma Diana (Faculty of Business and Management, 2020)
This study aimed to assess the service quality (SERVQUAL) dimensions toward customer satisfaction of Unifi in Selangor. The study was carried out by using quantitative methodology and service quality model with a total of 172 respondents. The research objective, research question and hypothesis were all set. Descriptive statistics, Multiple regression and Pearson correlation were used for data analysis and testing the hypotheses. The information was collected from the Unifi home user through online questionnaires, Google Form. Convenience sampling was utilized to collect data from respondents that use Unifi home (Sekaran, 2003). The research indicated that there is a relationship between service quality and customer satisfaction. Sekaran (2003) stated using Multiple regression analysis, result shows that two dimension of SERVQUAL (tangibility and reliability) are revealed significant impact on customer satisfaction while responsiveness, assurance and empathy have no impact on customer satisfaction. Besides, the most influential factors toward customer satisfaction is reliability dimension.